Factors associated with conjugal violence in the emergency center woman - Arce Cano, Raúl (2019)
The factors associated with conjugal violence are determined in the Wo-men’s Emergency Center (CEM) in the months of January to August in the year 2017. For this, a non-experimental, descriptive, cross-sectional study was conducted, where the study population was constituted by people who suﬀered some type of violence and were attended in the central headquarters CEM, Lima in the year 2017 in the months of January to August, the sample was probabilistic and comprised 186 people. For the bivariate analysis the Chi-square test was applied, in the same way the binary logistic regression was used to calculate Odds Ratio (OR) with 95 %conﬁdence intervals. The factors that were signiﬁcant with spousal violence are the psychological factor and the occupation of the victims, it is shown that those with personality disorder are 5 times more likely to suﬀer sexual violence than people who suﬀer from inadequate self-esteem, as well as people with Personality disorders are 16 times more likely to suﬀer psychological violence than people who have low self-esteem.